Flexible nano-film assisted aluminum alloy friction stir welding process
By combining solution casting of flexible TiC-TiB2 nanoparticle composite films with a cooling medium, the problem of uniform distribution of nanoparticles in aluminum alloy friction stir welding was solved, which improved the hardness and shear strength of the weld and enhanced the uniformity of the microstructure.
Patent Information
- Application Number
- CN202511180470.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-22
- Publication Date
- 2025-11-07
AI Technical Summary
During the friction stir welding process of aluminum alloys, problems such as microstructure segregation, grain growth, and uneven precipitation of the second phase are prone to occur in the weld zone, leading to a decline in weld performance. In addition, traditional methods of introducing nanoparticles have problems such as agglomeration, segregation, and contamination, which increase the difficulty and cost of application.
A flexible TiC-TiB2 nanoparticle composite film was prepared by solution casting. Combined with a cooling medium and reflow process, the nanoparticles were uniformly distributed and slowly released in the weld seam, which promoted the heterogeneous nucleation efficiency and refined the grains.
It improves the hardness and shear strength of the weld, enhances the uniformity of the weld structure, reduces the grain size, and improves the overall performance of aluminum alloy friction stir welding.
Smart Images

Figure CN120901457A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application relates to a flexible nanometer film assisted aluminum alloy friction stir welding process and belongs to the technical field of friction welding. BACKGROUND
[0002] Aluminum alloy is widely used in engineering fields such as aerospace, rail transit, new energy vehicles and lightweight equipment due to its low density, high strength, good corrosion resistance and other characteristics. Friction stir welding is a welding method suitable for various aluminum alloy structures, which has the advantages of high connection quality, small deformation and no molten pool defects. However, during the aluminum alloy friction stir welding process, problems such as organization segregation, grain growth and uneven second phase precipitation easily occur in the weld zone, which significantly reduces the performance of the weld and causes the so-called "weld softening zone" phenomenon.
[0003] In order to improve the service performance of the weld zone, researchers attempt to introduce nanoparticles as a strengthening phase during welding. Common nanoparticles include SiC, Al2O3 and TiC, but the traditional introduction method of nanoparticles has problems such as particle agglomeration, segregation, difficult control of addition amount and surface contamination of particles, which reduces the strengthening effect of nanoparticles and even further deteriorates the performance of the weld. In addition, the addition of nanoparticles has high dependence on equipment, which increases the difficulty and cost of actual industrial application.
[0004] Therefore, there is an urgent need to provide an aluminum alloy friction stir welding enhancement technology that does not change the existing equipment and can achieve uniform introduction of nanoparticles. SUMMARY
[0005] Therefore, the application provides a flexible nanometer film assisted aluminum alloy friction stir welding process, which introduces a flexible TiC-TiB2 nanoparticle composite film in the lap joint area of aluminum alloy plates, realizes the precise release and uniform distribution of nanoparticles in the weld without changing the existing welding equipment.
[0006] Specifically, the application is realized by the following scheme: A flexible nanometer film assisted aluminum alloy friction stir welding process, the steps are as follows: Step 1: Stirring polyvinyl alcohol and deionized water to form a transparent viscous polyvinyl alcohol-water mixed solution; Step 2: Put the TiC and TiB2 nanoparticles into a high-energy ball mill for ball milling, reduce the proportion of coarse particles, and after surface activation, add aluminum powder and deionized water, ultrasonic dispersion to prevent nanoparticle agglomeration, and obtain a nanoparticle-aluminum powder-water mixture; Step three, slowly pour the nanoparticle-aluminum powder-water mixture into the solution obtained in step one, and fully stir to ensure that the nanoparticles are evenly dispersed in the mixed solution, obtaining a nanoparticle-aluminum powder-polyvinyl alcohol-water mixture; Step four, evenly coat the nanoparticle-aluminum powder-polyvinyl alcohol-water mixture on a flat glass plate, and use a full-automatic coating machine to evenly coat it on the flat glass plate. After coating is completed, the glass plate is placed in an oven for drying. After solidification, the film is slowly peeled off to obtain a flexible nanoparticle composite film with a thickness of 100-200 μm. Step five, cut the flexible nanoparticle composite film to a size suitable for the overlapping position of the two aluminum alloy plates to be processed, and place it at the overlapping position of the two aluminum alloy plates. Pre-press the aluminum alloy plates and the flexible nanoparticle composite film by static pressure to make the flexible nanoparticle composite film closely adhere to the aluminum alloy plates, effectively avoiding the formation of pores or other inclusions in the weld. Then, the two aluminum alloy plates are friction stir welded. The flexible nanoparticle composite film melts locally with the aluminum alloy plates, and the nanoparticles in the flexible nanoparticle composite film are released into the weld. Step six, keep the friction stir welding equipment unchanged, adjust the welding parameters of the friction welding for re-welding, and spray cooling medium to the weld area during the re-welding process to accelerate the cooling of the weld. This not only promotes the further uniform dispersion of the nanoparticles, but also effectively prevents the grain coarsening caused by long high-temperature residence time.
[0007] The above scheme first uses solution casting method to uniformly disperse TiC-TiB2 nanoparticles and aluminum powder in a polyethylene polymer matrix to prepare a flexible nanoparticle composite film. After cutting, it is placed in the welding area. Under the thermal-mechanical coupling action of the friction stir head, the nanoparticles are released in space. The nanoparticles wrapped in the film are combined with the base material, and the cooling and re-welding process is used to promote heterogeneous nucleation efficiency, reduce grain size, uniform weld structure, and improve the hardness and shear strength of the weld.
[0008] Further, as preferred: In step one, In the polyvinyl alcohol-water mixed solution, the mass percentage of polyvinyl alcohol is 4-5%. Too much polyvinyl alcohol will cause the polyvinyl alcohol to be unable to fully dissolve, and too little will affect the subsequent film-making process.
[0009] The stirring temperature is 85-90℃.
[0010] The polyvinyl alcohol-water mixed solution also contains a plasticizer. The plasticizer is any one of polyethylene glycol, glycerol, and triethyl citrate.
[0011] The addition amount of the plasticizer is 7-12%.
[0012] The plasticizer acts to make the polystyrene alcohol softer and improve its compatibility with deionized water.
[0013] In step two, The mass ratio of TiC to TiB2 is 0.5-2:1. More preferably, the mass ratio of TiC to TiB2 is 1-1.5:1.
[0014] In the nanoparticle-aluminum powder-water mixture, the mass percentage of the nanoparticles is 0.01-0.05%, and the mass percentage of the aluminum powder is 0.1-0.3%. More preferably, the mass percentage of the nanoparticles is 0.03-0.05%.
[0015] The ultrasonic dispersion vibration frequency is 20-40 kHz, and the processing time is 30-60 min, which prevents the nanoparticles from agglomerating.
[0016] The ultrasonic dispersion can be performed using an ultrasonic disperser.
[0017] In step three, The stirring time is 45-60 min.
[0018] The stirring can be performed using a magnetic stirrer.
[0019] In step four, The coating speed is 5-10 mm / s.
[0020] The drying temperature is 40-60°C, and the duration is 1-1.5 h.
[0021] In step five, Before the aluminum alloy plate is overlapped, it is pretreated: the surface of the plate is cleaned using acetone, and then the plate is placed in an oven for drying, to ensure that the surface of the plate is free of oil stains and impurities. Preferably, the drying temperature is 40-60°C, and the duration is 1-1.5 h.
[0022] The parameters for the friction stir welding are set as follows: pre-welding angle: 1-3°, stirring head rotation speed: 1000-1200 r / min, welding speed: 60-80 mm / min, and shaft shoulder depression amount: 0.1-0.2 mm.
[0023] In step six, The parameters for the re-welding treatment are set as follows: pre-welding angle: -3--1°, stirring head rotation speed: 800-1000 r / min, welding speed: 25-40 mm / min, and shaft shoulder depression amount: 0.1-0.2 mm.
[0024] The cooling medium comprises the following components in the following volume ratios: Deionized water: 70-75, Ethylene glycol: 10~20, Sodium citrate: 5~6, Nonionic surfactant: 0.1~0.5.
[0025] The injection amount of the cooling medium is 200~300 mL / min.
[0026] The working principle of the application is as follows: the application realizes slow release and dispersion enhancement of nanoparticles in the aluminum alloy friction stir welding process by constructing a flexible TiC-TiB2 nanoparticle composite film based on a high polymer matrix. The flexible nanoparticle composite film is prepared by solution casting, the pretreated nanoparticles are uniformly dispersed in a polyvinyl alcohol solution, and a small amount of aluminum powder is compounded to improve the interface bonding capacity of the nanoparticles. The flexible nanoparticle composite film obtained by the method has good flexibility, can be accurately cut according to the size of the welding plate and placed in the welding area. In the process of friction stir welding, the flexible nanoparticle composite film softens and breaks under the thermal-mechanical coupling action of the stirring head, the internal TiC-TiB2 particles slowly release into the weld area with the flow of the welding molten metal, and are combined with the base material. Subsequently, by setting reasonable re-welding process parameters and temperature control, combined with external cooling medium, the uniform distribution of nanoparticles in the weld is further promoted.
[0027] In the above scheme, TiC and TiB2 as the strengthening phase have the advantages of high melting point, high hardness and high elastic modulus, which not only can significantly improve the comprehensive service ability of the matrix material, but also can be closely combined with the aluminum matrix interface, can act as a heterogeneous nucleation core, and can promote grain refinement. In the process of friction stir welding, the heat generated by the high-speed friction of the stirring head and the aluminum material melts the welding area of the plate, and the TiC and TiB2 nanoparticles in the film gradually release, as the preferential nucleation site for the precipitation of α-Al crystals, which improves the nucleation efficiency and reduces the grain size. In addition, the nanoparticles located at the grain boundaries can form a physical barrier to hinder the further growth of α-Al crystals.
[0028] Compared with the common particle and powder state adding method, the introduction method of nanoparticles in the application can improve the uniformity of the grain in the weld area, reduce the directionality of the structure, and effectively improve the shear strength of the weld. The application does not depend on an additional feeding system and does not need to change the welding equipment. The nanoparticles are added in the form of a film during welding, and only by controlling the material design and process parameters, the slow release of the nanoparticles in the film wrapping space is realized, and the cooling and re-welding process are completed to cooperatively control the structure and performance of the aluminum alloy friction stir weld. The application can be applied to the structure control and welding joint performance strengthening of various series of aluminum alloys, magnesium alloys and other low melting point metal materials. BRIEF DESCRIPTION OF DRAWINGS
[0029] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings needed to be used in the embodiments or prior art description will be briefly introduced. Obviously, the drawings in the following description are only some embodiments of the present application, and other drawings can be obtained by those skilled in the art without creative labor.
[0030] Figure 1 Microstructure of the weld after the welding of Example 1. DETAILED DESCRIPTION
[0031] In order to make the technical problems, technical solutions and beneficial effects of the present application more clearly understood, the technical solutions in the embodiments of the present application will be further described in detail below with reference to the drawings in the embodiments of the present application. It should be understood that the specific embodiments described here are only used to explain the present application and not to limit the technical solutions of the present application. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative labor are within the scope of protection of the present application.
[0032] It should be noted that when a component is referred to as "fixed to" or "disposed on" another component, it can be directly or indirectly on the other component. When a component is referred to as "connected to" another component, it can be directly or indirectly connected to the other component. The terms "up", "down", "left", "right", "front", "back", "vertical", "horizontal", "top", "bottom", "inner", "outer", etc. indicate the orientation or position based on the orientation or position shown in the drawings, and are only for the convenience of description, and cannot be understood as a limitation on the technical solutions.
[0033] In addition, the terms "first", "second" are only used for the purpose of convenient description, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of technical features. The meaning of "a plurality of" is two or more, unless otherwise specifically limited.
[0034] Performance test: The hardness test is detected by using a Vickers hardness instrument, and an aluminum alloy welding plate material of 200mmx80mmx3mm is used as a 5 series aluminum alloy plate material, and the chemical composition meets the national standard GB / T 3190-2020.
[0035] Example 1
[0036] The present embodiment provides a flexible nanometer film assisted aluminum alloy friction stir welding process, and the steps are as follows: (1) The polyvinyl alcohol powder is weighed and added to the deionized water, and then heated to 85℃ on a magnetic stirrer and continuously stirred for 40min.
[0037] (2) When the mixed solution becomes a transparent viscous liquid, turn off the magnetic stirrer, and after cooling to room temperature, add 1.5 ml of glycerol as a plasticizer and stir uniformly. The obtained solution is recorded as a polyvinyl alcohol-water mixed solution, in which the mass percentage of polyvinyl alcohol is 20%, and the mass percentage of plasticizer is 10%.
[0038] (3) Put TiC and TiB2 nanoparticles with a mass ratio of 3:2 into a high-energy ball mill and ball mill for 24 h.
[0039] (4) Add high-purity aluminum powder and TiC and TiB2 nanoparticles treated by spheroidization to deionized water, and use an ultrasonic dispersing instrument (power 750 W, vibration frequency 20 kHz) for treatment, with a treatment time of 30 min, to obtain a TiC-TiB2 nanoparticle-aluminum powder-water mixture.
[0040] (5) Slowly pour the TiC-TiB2 nanoparticle-aluminum powder-water mixture into the polyvinyl alcohol-water mixed solution, while using an electromagnetic stirrer (power 200 W) to stir, with a stirring speed of 300 r / min, and a stirring time of about 45 min to ensure uniform stirring, to obtain a TiC-TiB2 nanoparticle-aluminum powder-polyvinyl alcohol-water mixture. In the TiC-TiB2 nanoparticle-aluminum powder-polyvinyl alcohol-water mixture, the mass percentage of TiC and TiB2 nanoparticles is 0.03 wt%, and the mass percentage of aluminum powder is 0.2%.
[0041] (6) Pour the TiC-TiB2 nanoparticle-aluminum powder-polyvinyl alcohol-water mixture onto a flat glass plate, and use a full-automatic coating machine (power 2000 W) to evenly spread it on the glass plate, with a coating speed of 5 mm / s, to ensure that the film thickness is about 150 μm.
[0042] (7) Put the coated glass plate into an oven (power 200 W) to dry, dry at 40°C for about 1 h until it solidifies, and then slowly peel off the film to obtain a flexible nanoparticle composite film containing 0.03 wt% TiC-TiB2 nanoparticles.
[0043] (8) Take two aluminum alloy plates with a size of 200 mm x 80 mm x 3 mm, clean the surface of the plates with deionized water, and then put them into an oven (power 200 W) to dry at 40°C for about 1 h to ensure that the surface is free of oil stains and impurities. (9) Cut a flexible nanoparticle composite film with an appropriate area and place it at the joint of the two aluminum alloy plates, and use static pressure to pre-merge the plate-flexible nanoparticle composite film. (10) Stir-friction weld the two plates: Welding method: lap welding; welding angle: 3°, stirring head rotation speed: 1200 r / min, welding speed: 80 mm / min, shoulder depression amount: 0.1 mm.
[0044] (11) The equipment remains unchanged, and the friction stir welding parameters are adjusted for the auxiliary rewelding treatment, and during the rewelding process, a cooling medium is sprayed to the weld area at the rear of the stirring head for manual auxiliary cooling as the stirring head moves.
[0045] The process parameters for rewelding are as follows: welding angle: -3°, stirring head rotation speed: 1000 r / min, welding speed: 40 mm / min, shoulder depression amount: 0.1 mm.
[0046] The cooling medium is composed of 73.5% (volume percentage) deionized water, 20% ethylene glycol, 6% sodium citrate, and 0.5% non-ionic surfactant fatty alcohol polyoxyethylene ether (AEO), and the spraying amount is 300 mL / min. Spraying the cooling medium accelerates the cooling of the weld, not only promoting the further uniform dispersion of the nanoparticles, but also effectively preventing the grain coarsening caused by the excessive high-temperature residence time.
[0047] The weld of the welded product is detected, and the Vickers hardness (AHV) is 85.3, and the shear strength (TSS) is 12.7 kN.
[0048] Example 2
[0049] The settings of this example and example 1 are the same, except that in the flexible nanoparticle composite film, TiC:TiB2=2:1.
[0050] The weld of the welded product is detected, and the Vickers hardness (AHV) is 85.3, and the shear strength (TSS) is 12.7 kN.
[0051] Example 3
[0052] The settings of this example and example 1 are the same, except that in the flexible nanoparticle composite film, the volume ratio of TiC and TiB2= is replaced by 1:2.
[0053] The weld of the welded product is detected, and the Vickers hardness (AHV) is 85.3, and the shear strength (TSS) is 12.7 kN.
[0054] Example 4
[0055] The settings of this example and example 1 are the same, except that in the flexible nanoparticle composite film, TiC:TiB2=1:1.
[0056] The weld of the welded product is detected, and the Vickers hardness (AHV) is 85.3, and the shear strength (TSS) is 12.7 kN.
[0057] Example 5
[0058] The present embodiment is the same as the setting of Example 1, except that in the flexible nanoparticle composite film, TiC:TiB2=2:3.
[0059] The weld of the product after welding is detected, and the AHV is 83.1 and the TSS is 10.7 kN.
[0060] From the above Examples 1-5, it can be seen that under the same nanoparticle addition condition, as the ratio of TiC:TiB2 increases, the proportion of TiC gradually increases, and the AHV and TSS show a trend of first increasing and then decreasing, and the growth trend is more significant when TiC:TiB2=1:1-3:2, and is best when TiC:TiB2=3:2 (Example 1).
[0061] Comparative Example 1
[0062] The present comparative example is the same as the setting of Example 1, except that the nanoparticles are added by the traditional external method. The specific process is as follows: (1) Put the TiC and TiB2 nanoparticles with a volume ratio of 2:3 into a high-energy ball mill and ball mill for 24 h.
[0063] (2) Add high-purity aluminum powder and ball-milled TiC and TiB2 nanoparticles to deionized water, and use an ultrasonic disperser (power 750 W, vibration frequency 20 kHz) to treat for 30 min. The mass percentage of TiC-TiB2 nanoparticles is 0.03%, and the mass percentage of aluminum powder is 0.2%.
[0064] (3) Take two aluminum alloy plates with a size of 200 mm x 80 mm x 3 mm, clean the surface of the plates with deionized water, and then place them in an oven (power 200 W) at 40°C for about 1 h to ensure that the surface is free of oil and impurities; (4) Place the TiC-TiB2 nanoparticle-aluminum powder-water mixture evenly at the joint of the two aluminum alloy plates, and use static pressure to pre-merge the plate-TiC-TiB2 nanoparticle-aluminum powder-water mixture; (5) Perform friction stir welding of the two plates: Welding method: lap welding; pre-welding angle: 3°, stirring head speed: 1200 r / min, welding speed: 80 mm / min, shoulder depression amount: 0.1 mm.
[0065] (6) Keep the equipment unchanged, adjust the friction stir welding parameters for auxiliary rewelding treatment, and during the rewelding process, spray cooling medium to the weld area behind the stirring head for artificial auxiliary cooling.
[0066] The process parameters of back welding are as follows: pre-welding tilt angle: -3°, stirring head rotation speed: 1000 r / min, welding speed: 40 mm / min, and shoulder down pressure: 0.1 mm.
[0067] The cooling medium is composed of 73.5% (volume percentage) deionized water, 20% ethylene glycol, 6% sodium citrate and 0.5% non-ionic surfactant fatty alcohol polyoxyethylene ether (AEO), and the spraying amount is 300 mL / min.
[0068] Comparative Example 1 uses an external method to add nanoparticles, and the addition amount is the same as that of Example 5, but the nanoparticles are added in an external manner, which cannot achieve uniform addition and slow-release control of the nanoparticles. Therefore, not only is the service performance of the weld poor, with AHV being only 74.2 and TSS being only 8.2 kN, which is far lower than 83.1 and 10.7 kN of Example 5; but also the weld structure uniformity is poor.
[0069] Example 6
[0070] The settings of this example and Example 1 are the same, except that the mass percentage of nanoparticles in the flexible nanoparticle composite film is 0.01%, and TiC:TiB2=1:1.
[0071] The weld of the product after welding is detected, with AHV being 77.2 and TSS being 9.1 kN.
[0072] Example 7
[0073] The settings of this example and Example 1 are the same, except that the mass percentage of nanoparticles in the flexible nanoparticle composite film is 0.02%, and TiC:TiB2=1:1.
[0074] The weld of the product after welding is detected, with AHV being 80.6 and TSS being 9.4 kN.
[0075] Example 8
[0076] The settings of this example and Example 1 are the same, except that the mass percentage of nanoparticles in the flexible nanoparticle composite film is 0.04%, and TiC:TiB2=1:1.
[0077] The weld of the product after welding is detected, with AHV being 84.2 and TSS being 11.8 kN.
[0078] Example 9
[0079] The settings of this example and Example 1 are the same, except that the mass percentage of nanoparticles in the flexible nanoparticle composite film is 0.05%, and TiC:TiB2=1:1.
[0080] The product weld after welding was detected, and the AHV was 84.7 and the TSS was 12.1 kN.
[0081] Comparative Example 2
[0082] This comparative example was the same as the setup of Example 1, except that no nanoparticles were added. The specific process was as follows: (1) Polyvinyl alcohol powder was weighed and added to deionized water, then heated to 85°C on a magnetic stirrer and continuously stirred for 40 min.
[0083] (2) When the mixed solution became a transparent viscous liquid, the magnetic stirrer was turned off, and after cooling to room temperature, 1.5 ml of glycerol was added as a plasticizer and stirred evenly. The obtained solution was marked as a polyvinyl alcohol-water mixed solution, in which the mass percentage of polyvinyl alcohol was 20% and the mass percentage of plasticizer was 10%.
[0084] (3) High-purity aluminum powder was added to deionized water and treated using an ultrasonic disperser (power 750 W, vibration frequency 20 kHz) for 30 min to obtain an aluminum powder-water mixture.
[0085] (4) The aluminum powder-water mixture was slowly poured into the polyvinyl alcohol-water mixture while stirring using an electromagnetic stirrer (power 200 W) at a speed of 300 r / min for about 45 min to ensure uniform stirring, obtaining an aluminum powder-polyvinyl alcohol-water mixture. In the aluminum powder-polyvinyl alcohol-water mixture, the mass percentage of aluminum powder was 0.2%.
[0086] (5) The aluminum powder-polyvinyl alcohol-water mixture was poured onto a flat glass plate and uniformly coated on the glass plate using a full-automatic coating machine (power 2000 W) at a speed of 5 mm / s to ensure a film thickness of about 150 μm.
[0087] (6) The coated glass plate was placed in an oven (power 200 W) and dried at 40°C for about 1 h until it solidified, then the film was slowly peeled off to obtain a flexible composite film.
[0088] (7) Two aluminum alloy plates with a size of 200 mm x 80 mm x 3 mm were taken, the surface of the plates was cleaned with deionized water, and then placed in an oven (power 200 W) and dried at 40°C for about 1 h to ensure that the surface was free of oil and impurities; (8) The flexible composite film of appropriate size was placed at the joint of the two aluminum alloy plates, and the plate-flexible composite film was pre-merged using static pressure; (9) The two plates were friction stir welded: Welding method: lap welding; welding angle: 3°, stirring head rotation speed: 1200 r / min, welding speed: 80 mm / min, shoulder depression amount: 0.1 mm.
[0089] (10) keeping the equipment unchanged, adjusting the friction stir welding parameters to perform the auxiliary back-welding treatment, and in the back-welding process, spraying the cooling medium to the weld area at the rear of the stirring head to perform the artificial auxiliary cooling along with the movement of the stirring head.
[0090] The process parameters of the back-welding are as follows: welding angle: -3°, stirring head rotation speed: 1000 r / min, welding speed: 40 mm / min, shoulder depression amount: 0.1 mm.
[0091] The cooling medium is composed of 73.5% (volume percentage) deionized water, 20% ethylene glycol, 6% sodium citrate and 0.5% non-ionic surfactant fatty alcohol polyoxyethylene ether (AEO), and the spraying amount is 300 mL / min.
[0092] As can be seen from Comparative Examples 4 and 6-9, the Vickers hardness and the shear strength of the aluminum alloy plate friction stir welded joint are improved to different degrees with the addition of TiC-TiB2 nanoparticles. Under the same mass ratio of TiC to TiB2, the AHV and TSS increase with the increase of the addition amount of the nanoparticles, and the increase amplitude reaches the maximum when the addition amount of the nanoparticles is 0.03%. When the addition amount of the nanoparticles continues to increase, the AHV and TSS values can still steadily increase. Therefore, considering the cost and effect, the addition amount of the nanoparticles is preferably controlled in the range of 0.03-0.05%, and the addition amount of 0.03% of the nanoparticles is the best.
[0093] When the addition amount of the nanoparticles is 0.03wt% and the volume ratio of TiC to TiB2 is 3:2 (Example 1), the performance of the aluminum alloy welded plate is the best, the AHV is 85.3, and the TSS is 12.7 kN; the weld area has uniform structure and no obvious cracks (see Figure 1 ), which indicates that the addition of the nanoparticles can improve the uniformity of the weld structure.
[0094] The above-described examples only express several feasible implementation manners of the present application, and the description is relatively specific and detailed, but it should not be understood as a limitation on the patent scope of the present application. The examples do not limit the protection scope in the claims of the present application. For those skilled in the art, without departing from the concept of the present application, a number of modifications and improvements can be made, and any equivalent implementation or change made without departing from the present application should be included in the present application.
Claims
1. A flexible nanomembrane assisted aluminum alloy friction stir welding process, characterized in that, The steps are as follows: Step one, polyvinyl alcohol is added to deionized water to form a transparent viscous polyvinyl alcohol-water mixed solution by stirring; Step two, after the nanometer particles of TiC and TiB2 are treated by nodularization and surface activation, they are added to deionized water together with aluminum powder to obtain a nanometer particle-aluminum powder-water mixture by ultrasonic dispersion; Step three, the nanometer particle-aluminum powder-water mixture is slowly poured into the polyvinyl alcohol-water mixed solution, and fully stirred and dispersed to obtain a nanometer particle-aluminum powder-polyvinyl alcohol-water mixture; Step four, the nanometer particle-aluminum powder-polyvinyl alcohol-water mixture is coated and dried to obtain a flexible nanometer particle composite film, and the thickness of the flexible nanometer particle composite film is 100-200 μm; Step five, the flexible nanometer particle composite film is placed at the overlapping part of two aluminum alloy plates, and after pre-pressing, the aluminum alloy plates are welded by friction stir welding, and the flexible nanometer particle composite film is partially melted together with the aluminum alloy plates and releases the nanometer particles into the weld; Step six, the welding parameters of the friction stir welding are adjusted for re-welding treatment, and a cooling medium is sprayed to the weld area during the re-welding treatment to complete the friction stir welding.
2. A flexible nanomembrane assisted aluminum alloy friction stir welding process as claimed in claim 1, wherein: In the polyvinyl alcohol-water mixed solution, the mass percentage of polyvinyl alcohol is 4-5%.
3. A flexible nanomembrane assisted aluminum alloy friction stir welding process as claimed in claim 1, wherein: In step one, the stirring temperature is 85-90°C.
4. A flexible nanomembrane assisted aluminum alloy friction stir welding process as claimed in claim 1, wherein: In step one, a plasticizer is also added, and the plasticizer is one of polyethylene glycol, glycerol, and triethyl citrate, and the addition mass percentage is 7-12%.
5. A flexible nanomembrane assisted aluminum alloy friction stir welding process as claimed in claim 1, wherein: The mass ratio of TiC to TiB2 is 0.5-2:
1.
6. A flexible nanomembrane assisted aluminum alloy friction stir welding process as claimed in claim 1 or 5, wherein: In the nanometer particle-aluminum powder-water mixture, the mass percentage of nanometer particles is 0.01-0.05%, and the mass percentage of aluminum powder is 0.1-0.3%.
7. A flexible nanomembrane assisted aluminum alloy friction stir welding process as claimed in claim 1, wherein, In step five, the parameters of the friction stir welding are set as follows: pre-welding inclination angle: 1-3°, stirring head rotation speed: 1000-1200 r / min, welding speed: 60-80 mm / min, and shaft shoulder pressing amount: 0.1-0.2 mm.
8. A flexible nanomembrane assisted aluminum alloy friction stir welding process as claimed in claim 1, wherein: In step six, the parameters of the re-welding treatment are set as follows: pre-welding inclination angle: -3--1°, stirring head rotation speed: 800-1000 r / min, welding speed: 25-40 mm / min, and shaft shoulder pressing amount: 0.1-0.2 mm.
9. A flexible nanomembrane assisted aluminum alloy friction stir welding process as claimed in claim 1, wherein, The cooling medium comprises the following components in the following volume ratio: Deionized water: 70-75, Ethylene glycol: 10-20, Sodium citrate: 5-6, Non-ionic surfactant: 0.1-0.
5.
10. A flexible nanomembrane assisted aluminum alloy friction stir welding process as claimed in claim 1 or 9, wherein: The spraying amount of the cooling medium is 200-300 mL / min.